Hemopatch® with fibrin glue as a dural sealant in cranial and spinal surgery. A technical note with a review of the literature. (September 2020) - Montano, Nicola; Giordano, Martina; Caccavella, Valerio Maria; Ioannoni, Eleonora; Polli, Filippo Maria; Papacci, Fabio; Olivi, Alessandro
Highlights: First report on Hemopatch® with fibrin glue as a dural sealant in neurosurgery. First literature review about the use of Hemopatch® in neurosurgery. No CSF leak, no postoperative infection, no adverse reaction in this series. Using Hemopatch® with fibrin glue is safe and viable in cranial and spine surgery. Abstract: A major complication in cranial and spinal surgery is the post-operative occurrence of a cerebrospinal fluid (CSF) leak. Here we reported a technical note firstly describing the use of Hemopatch® with fibrin glue as a dural sealant in cranial and spinal neurosurgical procedures. Moreover we carried out a review of the literature. Further to the best of our knowledge this was the first series including patients submitted to different spinal surgeries in whom Hemopatch® was used as dural sealant. We prospectively collected the data of 22 patients. In all procedures, fibrin glue was applied after Hemopatch®. The mean age was 59.68 ± 10.79 years and the mean follow-up (FU) was 3.63 ± 1.46 months, respectively. Overall, Hemopatch® with fibrin glue was used in 8 cranial procedures (36.36%; all were retrosigmoid craniotomies) and 14 spinal procedures (63.64%). 9/14 spinal cases (64.28%) were incidental durotomies during a spinal decompression procedure. No CSF leak, no postoperative infection, no adverse reaction were observed during the FU in all cases. The literature search revealed only two retrospective series, reporting only patients submitted to cranial surgery for a total of 56 patients and a CSF leak occurring in 3 patients (5.35%). In conclusion, we firstly reported the feasibility and the safety of using Hemopatch® with fibrin glue as dural sealant in cranial surgery and different spinal procedures. Further larger comparative studies are needed to confirm our initial encouraging results.